In the physical to digital transition with friends—A story of performing inclusive research together no matter what life throws at you. (2nd August 2021) - Cook, Lilly; Rothstein, Pedro; Emeh, Lizzie; Frumiento, Pino; Kennedy, Donald; McNicholas, David; Orjiekwe, Ifeoma; Overton, Michaela; Snead, Mark; Steward, Robyn; Sutton, Jenny M.; Bradshaw, Melissa; et al.
Accessible summary: We are members of an arts organisation who support the creative talents of people with learning disabilities and autistic people. We have been working on a research project at "The Hub" at Wellcome Collection in a team consisting of academic and nonacademic professionals with diverse abilities. Because of coronavirus, we all had to stay home to stay safe. To carry on with our research project, we participated in 28 creative research meetings on Zoom. In this paper and accompanying video, we will tell you how we did it. We will also tell you how we felt about moving away from "The Hub" and trying to do research remotely from home. We hope our project has shown that people with learning disabilities can transition well to working online when there is trust and mutual respect. Abstract: Background: As part of "The Hub" project at Wellcome Collection, a team of eight co‐researchers with learning disabilities along academics created an online survey to challenge public understanding of learning disabilities. Using creative and arts‐based methods, co‐researchers remotely co‐analysed the survey results amid COVID‐19 lockdown challenges. Here, we explore our unexpected "transition" journey from the physical "Hub" to the digital space. Methods: We organised 20 sessions at The Hub and used audio/video/photo recordings to capture key moments. With the lockdown, we ensured that every co‐researcher had access to and support for digital technologies. Throughout 2020, we organised 28 Zoom meetings involving all co‐researchers. In June, Lilly (a multi‐media journalist and she lives by the motto striving for equal opportunities for people with disabilities and fairness throughout) and Sue (an independent Leadership Coach and Mentor) conducted Zoom interviews with the co‐research team to reflect on our transition journey. In this creative video‐form submission accompanied by an accessible report, Lilly puts together a story of how we transitioned and felt throughout this process. Findings: We identify that trust and the social bonds established at The Hub are the key components of our transition to the digital environment. There is the tension between longing for in‐person contact and trying to make the most out of the situation to maintain these relationships. At the heart of this is the motivation to "change the world" and strive for social justice. Having time and opportunity to improve, and co‐researchers' steady growth in confidence are equally important. Conclusions: The determination for maintaining friendships among co‐researchers and the motivation to "change the world" overcome COVID‐19‐related challenges in continuing co‐research.